HUBUNGAN DUKUNGAN ORANG TUA DENGAN MINAT BELAJAR PESERTA DIDIK MI/SD - Siti Masyitoh; Meiliana, Nikki (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Pupil interest plays a significant role in their level of engagement in the classroom, and engaged pupils have a higher chance of academic achievement. To gather pertinent data and data sources for this work, a qualitative technique connected to descriptive analysis is employed. Researchers used theories from different publications to conduct literature reviews to gather data sources, which they subsequently processed through analysis and conclusion-making. When children receive positive praise and encouragement from their parents at school, it can help them progress toward more good experiences. The interest of students in learning will grow as a result. Thus, it can be said that there is a strong correlation between pupils’ desire in studying and parental support.